Development of farmers' perception scale on agro tourism in Cameron Highlands, Malaysia - Kunasekaran, Puvaneswaran; Ramachandran, Sridar; Yacob, Mohd Rusli; Shuib, Ahmad (IDOSI Publications, 2011)
The purpose of this paper is to develop a scale to determine the farmers’ perception on agro tourism business. This paper presents the findings and development of key factors determining farmers’ perception on the agro tourism industry in Cameron Highlands, Malaysia. Attributes from previous research of local communities’ attitude were combined with newly found factors through an initial exploratory investigation to produce a new measurement scale. This combination of existing and new variables provided the platform to develop the scale. Factor analysis was used as the tool in the reduction method. The significant variables found were extracted and regrouped according to the appropriate factors in generating the new scale. As a result, 36 items were identified to have significant contribution in determining farmers’ perception on agro tourism that was regrouped into 9 factors. This finding can be used in determining farmers’ perception on agro tourism. The scale on farmers’ perception on agro tourism also would be essential to conduct further studies in this particular area of research.